Multiple-Pole Solutions to a Semidiscrete Modified Korteweg-de Vries Equation - Zhixing Xiao; Kang Li; Junyi Zhu (Advances in Mathematical Physics)
Multiple-pole soliton solutions to a semidiscrete modified Korteweg-de Vries equation are derived by virtue of the Riemann-Hilbert problem with higher-order zeros. A different symmetry condition is introduced to build the nonregular Riemann-Hilbert problem. The simplest multiple-pole soliton solution is presented. The dynamics of the solitons are studied.